Estimation of the effective elastic thickness using global gravitational, lithospheric structure, and rheology models - TENZER, Robert; ESHAGH, Mehdi; RATHNAYAKE, Samurdhika (Contributions to Geophysics and Geodesy, 2025)
Geodetic satellite missions become essential tools to predict the ocean-floor relief and study the oceanic lithosphere. Satellite-altimetry measurements of the sea surface topography are converted to marine gravity values that are used to predict bathymetric depths. This procedure requires information on marine sediment deposits as well as the lithospheric elastic thickness. Moreover, the elastic thickness provides information on the lithospheric strength in the context of interpreting tectonism and geological processes. In this study, we estimated the lithospheric elastic thickness beneath the Indian Ocean and surrounding continental regions by applying two methods that determine this parameter individually for the oceanic and continental lithosphere. For the former, we used global lithospheric age and upper-mantle temperature models. For the latter, we derived this parameter using global gravitational, lithospheric structure, and rheology models. Since our estimates are based on global models, the resulting map of the elastic thickness lacks more detailed features of lithospheric strength. Nevertheless, the principal pattern in elastic thickness variations relatively closely resemble tectonic configuration and lithospheric thermal state beneath the Indian Ocean. Active divergent tectonic margins along mid-oceanic rifts are characterized by a weak lithospheric strength. The strength increases due to cooling of the oceanic lithosphere with its age, while reaching maxima ∼50 km. A relatively weak lithosphere is found beneath Madagascar (15–30 km) and Sri Lanka (24–35 km). Within the domain of the Indian Ocean, the maximum elastic thickness (∼130 km) is detected beneath continental crustal fragments of the South Kerguelen Plateau.